Ewolucja nurtu neokonserwatywnego w polityce USA w wyniku zamachów z 11 września 2001 roku i jej konsekwencje - Milczanowski, Maciej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article showcases and examines the evolution of the neoconservative strand of US politics and its influence on the country’s international politics, with a particular analytical emphasis on the effects of the September 11, 2001 attacks and the ensuing counter-terrorism measures on the part of the USA. The importance of the neocon agenda has grown considerably in the wake of the WTC and Pentagon attacks and, as a result, has shaped the core of US Middle Eastern politics. Simultaneously, the neocon takeover of US politics marginalized the impact of both the conservative and the liberal circles. As a consequence, the US national security evolved into a hard power model based on military authority. Such a political practice yielded short-term profits (and – at best – media benefits and image gains) for the USA, but in the long run it also posed a threat to the West.
Evolution of neocons in us policy as a result of the September 11, 2001 attacks and its consequences
Keywords: neoconservatism; foreign policy; hard power; doctrine